Megatrends in food and agriculture technology, water use and nutrition - Traitler, Helmut; Dubois, Michel 1950-; Heikes, Keith; Petiard, Vincent; Zilberman, David 1947- (John Wiley & Sons, 2018)
Highlights and examines the growing convergence between the food and agricultural industries—the technological, environmental, and consumer-related drivers of this change, and the potential outcomes. This is the first book of its kind to connect food and the food industry with agriculture, water resources, and water management in a detailed and thorough way. It brings together a small community of expert authors to address the future of the food industry, agriculture (both for plants and animals), and water—and its role in a world of increasing demands on resources. The book begins by highlighting the role of agriculture in today's food industry from a historical perspective—showing how it has grown over the years. It goes on to examine water management; new ways of plant breeding not only based on genetic modification pathways; and the attention between major crops (soy, corn, wheat) and so-called "orphan crops" (coffee, cocoa, tropical fruits). The book then turns towards the future of the food industry and analyzes major food trends, the new food, and "enough" food; discusses possible new business models for the future food industry; and analyzes the impact that the "internet of everything" will have on agriculture and the food industry. Finally, Megatrends in Food and Agriculture: Technology, Water Use and Nutrition offers scenarios about how agriculture, food, and the food industry might undergo some radical transformations.--Provided by publisher.